Government Organization Development: Innovative Strategies with Makassar Metaverse - Malik, Ihyani (Journal of Local Government Issues, 2024)
Organizational development in the digital era requires innovative steps in adopting technology to maintain organizational sustainability and resilience . As an innovative step that attracts attention, using Makassar Metaverse as a platform is a strategic choice to strengthen the organization's position in the digital ecosystem. The purpose of this article is to present comprehensive research results, focusing on the concept of digital-based organizational development through the application of the Makassar Metaverse. The research method applied is quantitative with big data analysis to describe the impact and potential of this innovation on government organizations. The research results indicate that there are several challenges that need to be overcome, such as limited accessibility to government websites and the level of community involvement that is not yet optimal on government social media accounts. Nevertheless, the Makassar Metaverse innovation brings significant changes in the context of government organizational development. This initiative encourages information disclosure by the government and creates wider participation space for the public in the decision-making process of government organizations. Thus, this article illustrates how important Metaverse digital innovation is in supporting organizational transformation into an increasingly complex digital era.